Performing the Abhangas - Mumbai Archive Project Team (Jio Institute, 2024)
Abhanga is a form of devotional music and poetry narrated throughout the procession. The term ‘abhanga’ literally means ‘unbroken’ or ‘indestructible,’ symbolizing the eternal and continuous nature of devotion. They convey spiritual teachings, emphasizing the importance of inner purity, detachment, and the pursuit of moksha (liberation).